A complex mode of screen translation: the case of advertisements on Spanish television - Valdés, Cristina (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
This study on the translation of television commercials explores several aspects of this very specific audiovisual translation subtype. Firstly, it looks into dubbing and the language policies on Spanish television, which are issues affecting the decisions on the translation of television advertisements. Secondly, it approaches the notion of a TV ‘spot’ as an audiovisual text whose main components, image and sound, form a cohesive unity that is meant to trigger a persuasive effect, but may vary in translation. Finally, it analyses an example of a television spot, in English and in Spanish, focusing on the manipulation of the text when it is translated for Spanish television channels.